Effective traceability management: the global track&trace system - Pizzuti, Teresa; Pagnotta, Leonardo; Mirabelli, Giovanni (My University, 2013)
The evolution of the information technologies and their impact in human life promotes an increasing demand of reliable information when security and safety plays a primary role. Nowadays, food traceability represents one of the main concerns for public authorities and industries. In particular, traceability has become a critical part of the agro-food industry. The aim of the agro-food traceability is to allow the full monitoring of a product in the supply chain and to trace the history of a good from the producer to the consumer. It is therefore a preventive instrument of quality and safety management. The proposed research study is oriented to the definition of a new Global Track and Trace (T&T) System in which the entire world’s partners of a product’s supply chain are involved. In this system the functionalities of a conventional traceability system are combined with the functionalities of a Food Ontology for the traceability domain. The Food Ontology is defined in order to solve the issue of information-systems integration and standardization. The idea is to recover and to have available in a short time period all the relevant information about a product. This is a critical issue especially in case of foodborne outbreak and food crisis. The proposed framework can be a strategic approach for information and process management, also at the farm level. The model permits the Supply Chain optimization and the food quality management. The system itself can be a valuable tool for assuring customers and promoting the liability of the production process, along with the compliance with the regulatory standards aimed at defining quality and safety requirements.
Dottorato di Ricerca in Ingegneria Meccanica, XXVI Ciclo,a.a. 2013
Keywords: Ingegneria meccanica; Tracciabilità; Prodotti agroalimentari